PROFILE OF HIGH TOUCH IN THE APPLICATION LEARNING PROCESS - Mashari, Ali (Universitas Muhammadiyah Metro, 2015)
Abstract: This research generally aims to get brief description of application high touch in learning process. This research is conducted by descriptive quantitative method. The population is all teachers and students at senior high school. Samples are taken by using stratified cluster random sampling technique. The percentage, correlation and t test. The results of this research reveal that application high touch in learning process less and teachers’ opinion about high touch implementation as implication of teachers’ understanding toward learning process differ significantly with students’ opinion. In general, teachers’ opinion score is higher compared with student’s opinion scoreKeywords: high touch, learning process, students